MARCELY VALOIS, FERNANDO Z. VAZ-DE-MELLO & FERNANDO A. B. SILVA (2015) A taxonomic review of the Neotropical genus Hansreia Halffter & Martínez, 1977 (Coleoptera: Scarabaeidae, Scarabaeinae). Zootaxa, 4027: 205–226. - Valois, Marcely; Vaz-De-Mello, Fernando Z.; Silva, Fernando A. B. (Zootaxa, 2017)
In reviewing the taxonomy of the genus Hansreia Halffter & Martínez, 1977 three new species were described: H. krinskii, H. grossii and H. peugeoti. However, the collection where the holotype of H. peugeoti is deposited was not indicated (Valois, Vaz-de-Mello & Silva, 2015). According with ICZN (1999), this information is necessary to availability of a new specific and subspecific name published after 1999 (Article 16.4.2). Therefore, here we address the necessary information on the collection data of the holotype of H. peugeoti, currenty deposited in the CEMT (Seção de Entomologia da Coleção Zoológica, Departamento de Biologia e Zoologia, Universidade Federal de Mato Grosso, Cuiabá, Brazil):